Study of the Solidification Microstructure and Deformation Behaviour of Cu20Fe Alloy - Wenyong Niu; Su Huang; Baosen Lin; Jianping Li (Metals)
In this paper, the solidification microstructure characteristics of metastable immiscible Cu20Fe alloys under natural cooling conditions and subsequent cold rolling were analysed. The findings demonstrate that the Cu20Fe alloy underwent a liquid–solid transformation under natural cooling conditions. The equiaxed Cu matrix and the Fe dendrites exhibited elongation into ribbon-like structures parallel to the cold rolling direction. Following cold rolling, the mean grain size of the Cu20Fe alloy was considerably refined, and the mechanical properties were improved. After cold rolling, the Cu matrix formed both {112}<111> copper and {110}<112> brass textures. Furthermore, the strengthening mechanisms of the cold-rolled Cu20Fe alloy are primarily dependent on the strengthening of grain boundaries and work hardening. This provides an economically friendly method for the preparation of Cu-Fe alloys with high Fe compositions.